Identification of Settlements Quality in Pekanbaru Slums - M. Amin Sunarhadi; D Dahroni; P Priyono (Forum Geografi, 2005)
One of human basic needs is housing with high competitive situation caused increasing need of housing, spatial restriction, and economics factors. These influence to decreasing of housing quality then consequence to slums settlement. Undistributed population at Pekanbaru shown at Tangkerang Utara, Teluk Leok, and Meranti Pendak where slums are growing up. The aim of this stucdy is identifying slums area in Tangkerang Utara, Teluk Leok, and Meranti Pandak with spatial, complexity, and environmental approach. Data collected as primary and secondary data. Then are 28 indicators to identified slums area and classified quality of settlements. Results of this study shown that Tangkerang Utara have Medium Quality with typology as slums at center city, Teluk Leok have Low Quality with typology as slums at river side, and Meranti Pandak have Medium Quality with slums at urban fringe. This study also found that slums in Pekanbaru have spatial associated with low housing quality, community with low economic capacity, high density of population and building, bad sanitation, susceptible of fire and natural hazard, weakness of spatial planning implementation, and insufficient ratio of environmental settlement infrastructure. In pekanbaru, slums growth as continuous process.